2013
DOI: 10.2298/vsp1302177m
|View full text |Cite
|
Sign up to set email alerts
|

Age-related structural changes in the myenteric nervous plexus ganglion along the anterior wall of the proximal human duodenum: A morphometric analysis

Abstract: Aging does not induce changes in size and surface of neurons in the ganglia, but it decreases the number of neurons. The nerve structures in the elderly are partly emptied of bodies of nerve cells ("empty ganglions"), which indicates the existence of changed myenteric ganglia in the duodenum. These changes could be related to the duodenum motility disorder associated with aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…No gender-specific differences were observed. Similar to this observation, in human duodenum/jejunum samples from older individuals (65-84 years, n = 10), ganglion structures were often found with no nerve cell bodies due to loss of neurons, but the surface area of the ganglion structures of the MP per se did not decrease [22,23].…”
Section: Morphological Changes Of the Aging Enssupporting
confidence: 73%
See 1 more Smart Citation
“…No gender-specific differences were observed. Similar to this observation, in human duodenum/jejunum samples from older individuals (65-84 years, n = 10), ganglion structures were often found with no nerve cell bodies due to loss of neurons, but the surface area of the ganglion structures of the MP per se did not decrease [22,23].…”
Section: Morphological Changes Of the Aging Enssupporting
confidence: 73%
“…Many studies suggest that aging results in a loss of myenteric neuronal density [19,22,23,26,[29][30][31]34,41,46,47,51,54] and number [29,32,46,52] (see Table 1). For example, Mandic et al showed a decrease in the number of myenteric neurons per cm 2 by 25.93% in the aged group (65-84 years) compared to the youngest group (20-44 years) and by 23.32% in relation to the middle-aged group (45-64 years) [22].…”
Section: Aging Ens Leads To Age-related Gi Innervation Changesmentioning
confidence: 99%
“…In our study, in serosa number of enteric ganglia was decreased in early weeks, increased in midweeks and decreased in late weeks, in between the muscle layers they were increased in early and midweeks and decreased in late weeks whereas in submucosa (p = 0.01) they were decreased in early weeks and increased in mid and late weeks. Our study showed that there is fluctuation in the number of enteric ganglia as the gestational age progresses but age-related studies described that there are empty ganglia with less number of neurons 17 , 18 and studies in gastrointestinal diseases described that there is decrease in the number of ganglia. 19 …”
Section: Discussionmentioning
confidence: 46%
“…102 Within human small intestine, no agedependent changes were found in surface area of enteric ganglia within the duodenum, but the number of neurons was smaller (~16%) within the elderly (65-84 years; n = 30 donors but distribution among different age groups not stated). 116 By contrast, an increased number of NOS-expressing myenteric neurons were reported in terminal ileum of the elderly (78-86 years; n = 8 vs. n = 7 younger adults; all with cancer of ascending colon 117 ).…”
Section: Myenteric Plexusmentioning
confidence: 94%